Basic isoferritin and hypercalcaemia in renal cell carcinoma. Issue 9 (September 1982) - Mufti, GJ; Hamblin, TJ; Stevens, John
Abstract : A 63-year-old man with iron loss anaemia and hypercalcaemia was found to have a renal cell carcinoma. Despite the iron-deficient blood and bone marrow picture, the serum ferritin concentration was markedly raised. This was mainly due to a "basic isoferritin". The serum parathormone concentration was normal. The serum ferritin and calcium concentrations returned to normal after the tumour was removed. We propose that the renal cell carcinoma cells in this patient secreted the basic isoferritin as well as humoral factor(s) responsible for hypercalcaemia.